Cultural heritage information : access and management - Ruthven, Ian, 1968-; Chowdhury, G. G. (Gobinda G.) (IResearch series, 2015)
"Recent developments in the ICT, web and mobile technologies have significantly boosted research and development activities aimed at the creation and management of digital cultural heritage resources. Managing digital cultural heritage involves a number of challenges ranging from the digitization of cultural heritage objects and artefacts to various knowledge organization challenges that include metadata, indexing and retrieval, and various user and social challenges such as information seeking and retrieval in the context of cultural heritage, digital divide and social inclusion, social and legal policy issues, and moreover long term access and sustainability issues . Beginning with an overview of different information management issues and challenges associated with cultural heritage information, this book provides an account of research in digital cultural heritage focusing particularly on the knowledge organization, access, users and usability issues digital cultural heritage information systems and services."--Publisher description